If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x)(x + 5) = 204 Reorder the terms: x(5 + x) = 204 (5 * x + x * x) = 204 (5x + x2) = 204 Solving 5x + x2 = 204 Solving for variable 'x'. Reorder the terms: -204 + 5x + x2 = 204 + -204 Combine like terms: 204 + -204 = 0 -204 + 5x + x2 = 0 Factor a trinomial. (-17 + -1x)(12 + -1x) = 0Subproblem 1
Set the factor '(-17 + -1x)' equal to zero and attempt to solve: Simplifying -17 + -1x = 0 Solving -17 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + -1x = 0 + 17 Combine like terms: -17 + 17 = 0 0 + -1x = 0 + 17 -1x = 0 + 17 Combine like terms: 0 + 17 = 17 -1x = 17 Divide each side by '-1'. x = -17 Simplifying x = -17Subproblem 2
Set the factor '(12 + -1x)' equal to zero and attempt to solve: Simplifying 12 + -1x = 0 Solving 12 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 0 + -12 -1x = 0 + -12 Combine like terms: 0 + -12 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12Solution
x = {-17, 12}
| 64t^4-48t^4-4t^2+3=0 | | 11d=11d-8 | | 21x^2+13x-20=0 | | -84=-8+2(2-8k) | | 14-3z=-3z+14 | | a(-2ab)= | | 54x+27y=x | | f(4x)=4x^2-11 | | 15-7p=-17p-15+10p | | 14x+71x=x | | 2vw-2w= | | 12x-(5x-12)=1+6x | | f(x)=2x^2-3x-1 | | 9+13j=13j+2 | | a(a^2-2ab+b^2)= | | 2(x+2)x=6 | | 0.5x-y=2 | | -4+10t=-2-10t+20t | | (X+93)=4x | | 17(9-x)-5=52 | | 0=-4u+4u | | 10g-3=10g-2 | | 7x-28=4 | | 7x-28=48 | | -(1-8x)=31+4x | | -5n+9-4=-5n+5 | | 14mn+18m= | | 9x-5=45 | | -7(2x-1)+5(3x-2)-7=4-9 | | 7+5k=5k+1 | | 2x-3=8x-3(1+2x) | | 3x+7=-2x+5 |